PENDEKATAN EKONOMI HIJAU DALAM PENGELOLAAN REDUKSI EMISI KARBON OLEH TUMBUHAN DI KOTA CILEGON - Mahdani, Mahdani; Muhlisin, Muhlisin; Masyruroh, Anis; Damayani, Febiana Eka (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2024)
CO2 emission reduction is the main instrument to promote green growth in developing countries such as Indonesia. Carbon dioxide emissions from the transportation sector are a main contributing factor. Cilegon City with its high industrial and transportation activities, as well as limited public green spaces, contributes to this. Cilegon City protocol roads include Jalan Ahmad Yani, Jalan S.A Tirtayasa, and Jalan Jendral Sudirman. This research aims to analyze the amount of CO2 emissions generated by motorized vehicles, analyze the absorption capacity of vegetation in absorbing CO2 emissions from motorized vehicles and proper greening planning to maximize the reduction of CO₂ emissions from motorized vehicles on the Cilegon City Protocol Road. The research method uses quantitative with a descriptive approach, some of the analysis includes energy ecological footprint analysis, vegetation absorption analysis, and greening planning. The results obtained total CO2 emissions on the Cilegon City Protocol Road amounted to 4,400.003 tons / year. There are 8,016 plants on the Cilegon City Protocol Road with a vegetation absorption capacity of 395.328 tons/year. The remaining unabsorbed emissions amounted to 4004.68 tons/year. Greening planning is carried out by adding vegetation, government policies and collaboration between the government and the community. The addition of vegetation on the Cilegon City Protocol Road is 692 plants from the addition shows the potential to increase carbon dioxide absorption by 101.43%.